Evolution Toward the Observational Features of a Stripped Envelope Type IIb Supernova in a Binary System. (1st May 2022) - Long, Gang; Song, Han-Feng; Zhang, Rui-Yu; Qin, Ying; Zhao, Liu-Yan; Qi, Shi-Tao; Wu, Fang-Wen
Abstract: Type IIb supernovae (SNe IIb) that have a thin layer of hydrogen left in their outer envelope have been believed to belong to core collapse supernovae. Mass transfer via Roche lobe overflow can significantly change the nucleosynthesis and surface chemical elements of the progenitors of SNe IIb. We aim to explore what conditions a close binary can meet with the observational features of SNe IIb. We find that an observed low mass SN IIb cannot be produced by a low mass isolated star with M < 20 M ⊙ due to the existence of a thick hydrogen envelope regardless of rotation. Binaries dominate as progenitors in the mass interval (i.e., M < 20 M ⊙ ) considered in this paper. The 16 M ⊙ primary with a 14 M ⊙ companion in a binary system with ∼10 days < P orb < 720 days can reproduce observational features of SNe IIb (i.e., T eff, log L / L ⊙, M He, M H, etc.). With the decrease of the hydrogen-rich envelope mass, the radius of the progenitor shrinks. The associated types of SN IIb progenitors from RSGs and YSGs to BSGs are closely related to the amount of hydrogen left in the envelopes. Rotation can bring the production of the CNO reaction to the stellar surface at an early phase, which would explain the nitrogen-rich circumstellar material of SN 1993J and can also explain the large He/H ratio of supernova ejecta. Rotation can increase the corresponding region of the orbital period which can produce an SN IIb.